Ocean acidification does not alter grazing in the calanoid copepods Calanus finmarchicus and Calanus glacialis. (13th December 2015) - Hildebrandt, Nicole; Sartoris, Franz J.; Schulz, Kai G.; Riebesell, Ulf; Niehoff, Barbara
Abstract: It is currently under debate whether organisms that regulate their acid–base status under environmental hypercapnia demand additional energy. This could impair animal fitness, but might be compensated for via increased ingestion rates when food is available. No data are yet available for dominant Calanus spp. from boreal and Arctic waters. To fill this gap, we incubated Calanus glacialis at 390, 1120, and 3000 µatm for 16 d with Thalassiosira weissflogii (diatom) as food source on-board RV Polarstern in Fram Strait in 2012. Every 4 d copepods were subsampled from all CO2 treatments and clearance and ingestion rates were determined. During the SOPRAN mesocosm experiment in Bergen, Norway, 2011, we weekly collected Calanus finmarchicus from mesocosms initially adjusted to 390 and 3000 µatm CO2 and measured grazing at low and high pCO2 . In addition, copepods were deep frozen for body mass analyses. Elevated pCO2 did not directly affect grazing activities and body mass, suggesting that the copepods did not have additional energy demands for coping with acidification, neither during long-term exposure nor after immediate changes in pCO2 . Shifts in seawater pH thus do not seem to challenge these copepod species.